Art Activities Used by Mothers with Intellectually Disabled Children and Their Levels of Psychological Resilience: A Cross-sectional and Correlational Study - Musa Özsavran; Tülay Kuzlu Ayyıldız (Mediterranean Nursing and Midwifery, 2024)
Objective: Art activities are one of the essential methods used to strengthen the psychological resilience of individuals. This study aimed to determine the relationship between the artistic activity practices of mothers with intellectually disabled children and their psychological resilience levels. Method: This study used a cross-sectional and correlational research design. Personal information forms containing questions about mothers’ unique and artistic practices and adult resilience scale (ARS) were used in data collection. SPSS 25.0 program was used to evaluate the data. The resulting relationships were assessed by regression analysis. Results: While 76.7% of mothers relax with the art activities they use, 62% practice art activity methods with their children. Too many mothers-73.6% of them-cannot find enough time for themselves. Mothers’ ARS scores were found to be high. Conclusion: Most mothers are interested in art activities. Therefore, psychological resilience scores were also found to be high. While there was a positive and significant relationship between the mothers’ ARS scores and their age, there was a meaningful negative relationship between the total number of mentally disabled children.